Hospital Militar Psicoterapeutico de Tame (2020)
the aim is to carry out the rehabilitation of the Yopal - Arauca axis, in which 3 main towns are taken as development nodes: Arauca, Tame and Yopal, in which the territory will be improved with strategies such as the improvement of airports, improvement of highways (infrastructure), the education, health, housing, among others, to improve the development of this axis in order to mitigate the problems that it has, being one of the main ones, such as the armed conflict.